Home equity insurance - Wood, Gavin; Sommervoll, D. (Emerald Group Publishing Limited, 2011)
Purpose – This paper aims to study to what extent an insurance based on a house price index provides equity protection for homeowners. Design/methodology/approach – The paper uses a novel dataset of all housing market transactions in the metropolitan area of Melbourne 1990-2006, to construct repeated sales indices of various temporal spatial aggregation. These indices are used to discuss the efficiency of index-based insurance schemes. The paper also considers efficiency under different specifications of legitimate claims. Findings – It is found that the payout efficiency is surprisingly stable (around 50 percent) for all temporal spatial aggregations. A neighborhood index outperforms the metropolitan index with respect to target efficiency (the probability of payout given a loss). The introduction of maturity times, say legitimate claim five years after purchase, does improve efficiency somewhat. However, the idiosyncratic component of housing market transactions remains high, and the insurance probably unattractive from a homeowner perspective. Originality/value – To the authors’ knowledge, this is the first time an index-based insurance scheme is analyzed using real-market transactions.